Caribbean Report 08-06-1995 - Ransome, Debbie (anchor); John, Velon (interviewee); Ninvalle, Pete (correspondent); Compton, John (interviewee); Newman-Williams, Marjorie (interviewee); Trevena, Claire (correspondent); Gration, Harry (correspondent); Bairstow, David (interviewee); Fraser, Tony (correspondent); Roycroft-Davis, Chris (interviewee) (The British Broadcasting Corporation, 1995)
This report looks at the Opposition in St. Lucia which is seeking to file a writ of prohibition against the national budget. UNICEF publishes its annual report, The Progress of Nations and the Caribbean Director Marjorie Newman-Williams comments on how the region measures up against the international trends. UNICEF's findings indicate that structural adjustment has seriously undermined the quality of care of children in the Caribbean. Three Caribbean nationals contesting the poll at Canadian provincial elections. In Jamaica, the Minister of National Security and Justice, K.D. Knight suggests the introduction of a night court system to tackle the severe backlog in the justice system. In cricket, the West Indies is on top after day one of the first test against England in Headingley. Meanwhile, the British press is interested in the claims of a voodoo curse against West Indies batsman, Brian Lara. Tony Fraser reports on what is the truth behind the story.
1. Headlines with Debbie Ransome (00:00-00:26)
2. St. Lucia Opposition challenges preparations for the national budget (00:27-02:56)
3. UNICEF warns of the effects of structural adjustment on the region's children (02:57-07:14)
4. Three Caribbean nationals are contesting the poll in Canada's provincial elections (07:15-09:30)
Keywords: Saint Lucia -- Politics and government; Budgets -- Saint Lucia; Children -- Caribbean Area -- Social conditions; Fertility, Human -- Caribbean Area; Teenage pregnancy -- Caribbean Area; Elections -- Canada; Canada -- Politics and government; Court congestion and delay -- Jamaica; Courts -- Jamaica; Justice, Administration of -- Jamaica; Cricket -- Tournaments -- England; Cricket -- West Indies; Cricket -- Press coverage -- Great Britain; British newspapers -- Headlines; Cricket players -- West Indies; Voodooism